Perancangan Sistem Informasi Akuntansi Penerimaan Kas pada SD Islam Pondok Duta - Hapsari Widayani; Sepni Yanti; Ahmad Fahrudin (Peneliti.net, 2020)
The The purpose of this study is to determine the process of design the accounting information system of cash receipts in SD Islam Pondok Duta so that it can help a more computerized so that it can help a more computerized for process of cash receipts and make the accurate financial reports. The data collection method was carried out by direct observation to the research object, that is SD Islam Pondok Duta. System development method are planning of the system stage, the analysis of the system stage, design of the system stage, implementation of the system stage, and testing and use of the system stage.The result of the research is the process of cash receipt and record in SD Islam Pondok Duta still uses a manual system so that a computerized system is made. The procedure for cash receipts In SD Islam Pondok Duta begins with the students bring their tuition cards and deposit their money. The next process is the treasurer to make proof of receipt of money. After the payment process has been completed, the treasurer combines all proof of receipt The proof of receipt is combined to make it easier for the treasurer to make two sets of cash receipts reports for each transaction that occurs.This cash receipts report will be submitted to the principal for review.After know the constraints that occur in the school, the authors design a system using a data flow diagram (DFD) and create a database with an entity relationship diagram (ERD) After all the things have gone through, the next process is to describe the design in a simple way.